HIGHER EDUCATION GOVERNANCE ANALYSIS (EMPIRICAL STUDY ON MUHAMMADIYAH UNIVERSITY IN JAKARTA) - Haris Sarwoko (PENANOMICS: International Journal of Economics, 2023)
Functioning of the role of group manager in the management of the organization can improve productivity. However, the function is also a phenomenon in the relationship between principals and agents, where there is a divergence of interests between owners and managers of organizations who then create the agency problem, because basically the agent has their own interests. This is where the role of control is needed to suppress agency problems. Departure from this idea, the research aim is to understand the mechanisms of control and rational behavior of agents in the practices of elections, financial reporting, and compensation. The study concludes: 1) the norms and cultural values appear to be more prominent than economic value in the control mechanism. Norms and values restrict the organization's behavior and justify the sanction for any inappropriate behavior in the system. Lack of commitment and socialization occur relatively high on the system of organization members who continually give up some or all personal interests to become a member of Muhammadiyah; 2) the rationality that is developed within the organization is a form of mental construction agent based on social experience, character local and specification. Muhammadiyah values tradition that was developed by Ahmad Dahlan have become the source of agent, especially in the rationalization measures gain legitimacy from the environment.